Design and Experimental Research of Lubrication System of High Power Transfer Case - Zhang Lei; Ge Kai; Shan Hongbo; Li Hongbiao; Zhao Yanming; Zhang Bin; Mu Lianhao; Gao Lili; Zhao Juan; Jiang Zhong (Jixie chuandong)
The high power transfer case as a key component of a multi-axis super-heavy chassis transmission system,with the characteristics of large torque,high speed,and large temperature difference,rely on splash lubrication and natural air cooling has been unable to meet the need of the chassis for high mobility,high through off-road and extreme ambient temperature. It is necessary to use the forced lubrication system to lubricate the internal hot spots of the transfer case,especially the bearing position. Therefore,the power thermal energy model of the hotspots of the transmission parts is built first,through the heat balance conditions,the flow demand of the lubrication point and the overall are estimated,and then a hydraulic simulation analysis model is established,the matching lubrication system piping is designed. Aiming at the problem of the natural air cooling can’t achieve the system thermal balance requirements in the great power of the transmission system,by calculating the surface wind speed and heat dissipation surface,the heat dissipation capacity of the transfer case itself is evaluated,the external air-cooled radiator and fan are matched according to the heat dissipation requirement.Finally,through the bench and running vehicle test,the design of the high power transfer case forced lubrication system to meet a multi-axis super-heavy chassis of the use of the requirements is verified.